Assessment of hydration process and mechanical properties of cemented paste backfill by electrical resistivity measurement. Issue 2 (3rd April 2018) - Xu, Wenbin; Tian, Xichun; Cao, Peiwang
Abstract: Cemented paste backfill (CPB) is an emerging mine backfill technique that allows environmentally hazardous tailings to return to the underground openings or stopes, thereby maximising the safety, efficiency and productivity of operation. Uniaxial compressive strength (UCS) is one of the most commonly used parameters for evaluating the mechanical performance of CPB; the prediction of the UCS of CPB structures from early to advanced ages is of great practical importance. This study aims to investigate the predictability of the UCS of CPB during the hydration process based on electrical resistivity (ER) measurement. For this purpose, the samples prepared at different cement-to-tailing ratios and solid contents were subjected to the ER test during the whole hydration process and UCS tests at 3, 7, 28 days of curing periods. The effect of cement-to-tailing ratio and solid content on the ER and UCS of CPB samples was obtained; the UCS values were correlated with the corresponding ER data. Microstructural analysis was also performed on CPB samples to understand the effect of microstructure on the ER data. The result shows that the ER of CPB decreases first and then increases with the speed which is faster in the previous part than the latter. The ER and UCS of CPB samples increased with increasing cement-to-tailing ratio and solid content and curing periods. A logarithmic relationship is established for each mixture in order to predict the UCS of CPB based on ER. Scanning electron microscope analyses have revealed that the microstructure of the CPB changes with the age from the initial floc to honeycomb, and eventually to the compact clumps. The ER properties of CPB samples were highly associated with their respective microstructural properties. The major output of this study is that ER test is effectively capable for a preliminary prediction of the UCS of CPB.